Chronotype in very low birth weight adults – a sibling study. (2nd July 2020) - Björkqvist, Johan; Kuula, Juho; Kuula, Liisa; Nurhonen, Markku; Hovi, Petteri; Räikkönen, Katri; Pesonen, Anu; Kajantie, Eero
ABSTRACT: Chronotype is the temporal preference for activity and sleep during the 24 h day and is linked to mental and physical health, quality of life, and mortality. Later chronotypes, so-called "night owls", consistently display poorer health outcomes than "larks". Previous studies have suggested that preterm birth (<37 weeks of gestation) is associated with an earlier chronotype in children, adolescents, and young adults, but studies beyond this age are absent. Our aim was to determine if adults born preterm at very low birth weight (VLBW, ≤1500 g) display different chronotypes than their siblings. We studied VLBW adults, aged 29.9 years (SD 2.8), matched with same-sex term-born siblings as controls. A total of 123 participants, consisting of 53 sibling pairs and 17 unmatched participants, provided actigraphy-derived data on the timing, duration, and quality of sleep from 1640 nights (mean 13.3 per participant, SD 2.7). Mixed effects models provided estimates and significance tests. Compared to their siblings, VLBW adults displayed 27 min earlier sleep midpoint during free days (95% CI: 3 to 51 min, p =.029). This was also reflected in the timing of falling asleep, waking up, and sleep-debt corrected sleep midpoint. The findings were emphasized in VLBW participants born small for gestational age. VLBW adults displayed an earlier chronotype than their siblings still at age 30, which suggests that the earlier chronotype is an enduring individual trait not explained by shared family factors. This preference could provide protection from risks associated with preterm birth. Abbreviations: AGA: Appropriate for gestational age; ELBW: Extremely low birth weight, ≤ 1000 grams; FMBR: Finnish Medical Birth Registry; HeSVA: Helsinki Study of Very low birth weight Adults; MSFsc: Midsleep on free days, corrected for sleep debt; SGA: Small for gestational age, ≤ −2 SD; VLBW: Very low birth weight, ≤ 1500 grams; WASO: Wake after sleep onset